2022
DOI: 10.3389/fsurg.2022.1047975
|View full text |Cite
|
Sign up to set email alerts
|

Bench surgery with autotransplantation for bilateral Wilms tumor—A feasible technique for renal sinus invasion

Abstract: PurposeBilateral Wilms tumor (BWT) with renal sinus invasion requires extremely difficult surgical care. This study presents an alternative strategy for tumor removal while at the same time preserving the renal parenchyma.Materials and methodsIn total, 9 cases of synchronous BWT were admitted to our hospital between May 2016 to Aug 2020. We retrospectively reviewed the clinical data, surgical technique, and functional and oncological outcomes of these cases.ResultsThe 9 cases included 3 males and 6 females, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…The present study indicates that tumors undergoing NSS ex vivo had a higher complexity compared with tumors undergoing NSS in vivo. Meanwhile, our previous study has found that NSS ex vivo was a feasible technique for BWT with renal sinus invasion [24]. Regardless of the surgical approaches, the surgical di culty remains the collecting system or sinus invasion.…”
Section: Discussionmentioning
confidence: 99%
“…The present study indicates that tumors undergoing NSS ex vivo had a higher complexity compared with tumors undergoing NSS in vivo. Meanwhile, our previous study has found that NSS ex vivo was a feasible technique for BWT with renal sinus invasion [24]. Regardless of the surgical approaches, the surgical di culty remains the collecting system or sinus invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Renal autotransplantation is performed for complex renal vascular diseases (renal artery aneurysms), extensive ureteric injuries, and conventionally unresectable renal tumors [6,11,12]. Several studies have reported that ex vivo PN and autotransplantation for highly complex renal tumors in solitary or bilateral multifocal kidneys result in excellent tumor control and preservation of renal function [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%